Pengaruh Pendekatan Kontekstual terhadap Prestasi Belajar Siswa pada Tema 1 Subtema 2 Kelas SD Negeri Sinaksak - Hotrin Sitohang; Lisbet N. Sihombing; Eva Pasaribu (Medan Resource Center, 2022)
This study aims to determine the improvement of student achievement in thematic learning specifically in theme I sub-theme 2 The research used is quantitative research because, because the problems brought are clearly related to data in the form of facts proven through observation and analysis using statistics. The population used is 54 students, the sample is 54 students. The variables in this study are the Contextual Approach (X) and learning achievement (Y). Data collection methods. data by test. The results and this study indicate that there is success in applying a contextual approach to student achievement in thematic subjects in the Sinaksak district public elementary school. The average pretest value of the experimental class is 54,629 while the average pretest of the control class is 54.629 The average posttest value of the experimental class is 82.77 while the control class is 74.77. It can be concluded that there is an effect of contextual approach on student learning achievement.